Health fest 2021: innovative approach to conduct community service learning - Chen, Xin Wee; Ismail, Zaliha (Faculty of Medicine, 2021)
Given the prolonged movement restrictions which have led to sudden lifestyle changes and rising mental health concerns, innovative health promotion approaches are inevitable. As an effort to safeguard the community health and well-being while ensuring the Community Service Learning (CSL) could be pursued during the COVID-19 pandemic, the Department of Public Health Medicine, Universiti Teknologi MARA (UiTM), has conducted a virtual ‘Health Fest UiTM 2021’ from 28th July to 8th August 2021.